Differences in Water-Soluble Intermediates from Slow Pyrolysis of Amorphous and Crystalline Cellulose - Liu, Dawei; Yu, Yun; Wu, Hongwei (American Chemical Society, 2013)
The paper reports the significant differences in the pyrolysis behavior between amorphous and crystalline cellulose. The strong hydrogen bonding networks in crystalline cellulose appear to preserve the sugar ring structure during pyrolysis so that the yield (a maximum of ~30% on a carbon basis at 250 °C) of water-soluble intermediates for amorphous cellulose is considerably higher than that (a maximum of ~3% on a carbon basis at 270 °C) of crystalline cellulose pyrolysis. Direct evidence was also provided to prove that various sugar oligomers (DPs: 1-14) present in water-soluble intermediates are indeed produced from some short glucose chain segments in amorphous cellulose during pyrolysis at a temperature as low as 140 °C. The weak hydrogen bonding networks in amorphous cellulose allow the liberation of these short glucose chain segments as pyrolysis intermediates. Compared to those from crystalline cellulose, the water-soluble intermediates from amorphous cellulose contain considerably more sugar oligomers and anhydro-sugar oligomers with a much wider range of degrees of polymerization (DPs), e.g., 1-14 and 1-16 for sugar oligomers and anhydro-sugar oligomers, respectively. Post-hydrolysis results, together with the yields of quantifiable sugar and anhydro-sugar oligomers, further suggest that water-soluble intermediates from amorphous cellulose pyrolysis at temperatures <270 °C are mainly contributed by high-DP sugar and/or anhydro-sugar oligomers, plus partially decomposed sugar-ring-containing oligomers, i.e., PDSRCOs. However, low-DP anhydro-sugar oligomers and PDSRCOs are the main products of water-soluble intermediates from crystalline cellulose pyrolysis. At higher temperatures (e.g., 300 °C), the water-soluble intermediates from amorphous cellulose are dominantly non-sugar products, largely due to the destruction of the sugar ring structures within the pyrolyzing amorphous cellulose.